In vivo targeting capacities of different nanoparticles to prostate tissues based on a mouse model of chronic bacterial prostatitis - Hu, Ruimin; Yang, Yang; Song, Guojing; Zhao, Fuhan; Chen, Saipeng; Zhou, Zhansong; Zheng, Jun; Shen, Wenhao (Frontiers in Bioengineering and Biotechnology, 2022)
Chronic bacterial prostatitis usually occurs in men and seriously affects the quality of life of patients. The efficacy of chronic bacterial prostatitis treatment is limited by the difficulty for free drugs (e.g., antibiotics) to penetrate the prostate epithelium and target inflammatory tissues. The advent of nanotechnology offers the possibility to address this issue, such as the development of targeted nanoparticle delivery strategies that may overcome these important limitations. The physicochemical properties of nanoparticles, such as particle size, shape and surface modification ligands, determine their targeting effectiveness. In this study, nanoparticles with different physicochemical properties were prepared to explore and confirm their targeting capacities to inflammatory prostate tissues of chronic bacterial prostatitis, focusing on the effects of size and different modification ligands on the targeting performance. In vivo and ex vivo imaging results verified that folic acid-modified nanoparticles with a particle size of 180-190 nm via tail intravenous injection had the optimal targeting efficiency to prostate tissues. Our results provide an experimental basis and reference value for targeted therapy of prostate-related diseases with nanotechnology in the future.